A new fully integrated X-ray irradiator system for dosimetric research - Richter, Daniel; Mittelstraß, Dirk; Kreutzer, Sebastian; Pintaske, Rainer; Dornich, Kay; Fuchs, Markus (Applied radiation and isotopes, 2016)
A fully housed X-ray irradiator was developed for use within lexsyg or Magnettech desktop equipment. The importance of hardening of the low energy photon radiation is discussed, its performance and feasibility is empirically shown and sustained by basic numerical simulations. Results of the latter for various materials are given for different X-ray source settings in order to provide estimates on the required setup for the irradiation of different geometries and materials. A Si-photodiode provides real-time monitoring of the X-ray-irradiator designed for use in dosimetric dating and other dosimetric application where irradiation of small samples or dosemeters is required.
Online veröffentlicht: 20. März 2016, Artikelversion: 31 März 2016
Gesehen am 26.03.2025